Influence of carbon dioxide at supercritical phase separating the omega-3 fish oil from sardine wastes following sharia compliant - Sahena, Ferdosh; Sarker, Md. Zaidul Islam; Yunus, Kamaruzzaman; Ab. Kadir, Mohd Omar (2017)
Sardine generally processed as canned fish and in consequence, a lot of solid wastes are generated as by-products which could be good sources of fish oil. Omega-3 fatty acids of total lipids extracted by supercritical carbon dioxide (scCO2) method from sardine fish wastes were determined and the results were compared with Soxhlet extraction method. Total wastes (head, skin, fin and viscera) of Sardinella fimbriata showed higher lipid content (7.68% dry wt.) compare to other species of sardine in our study. Highest oil (7.5% dry wt.) recovery were found in pressure swing technique followed by continuous technique of scCO2 at temperature 65 oC and pressure 40 MPa which is closure to the yield (7.68% dry wt.) of soxhlet method. The CO2 consumption was found lower at pressure swing technique compare to continuous method of scCO2. Docosahexaenoic acid (DHA) was characteristically major polyunsaturated fatty acids (PUFA) found in Sardinella fimbriata accounting 17.02% in head, 13.75% in viscera and 15.81% in total wastes of the fatty acids. Total oil extracted by scCO2 had lower free fatty acids content than the oil extracted by Soxhlet method. Pressure swing method of scCO2 was found attractive technique due to high oil recovery, low CO2 consumption, less extraction period and better quality of oil.